Age-related changes in cerebral oxidative metabolism - Hoyer, Siegfried (Drugs & aging, 1995)
Glucose metabolism in the brain is of central significance. It contributes to the synthesis of the neurotransmitters acetylcholine, glutamate, aspartate, γ-aminobutyric acid (GABA) and glycine, and yields adenosine triphosphate (ATP) as the driving force of almost all cellular and molecular work. Neuronal glucose metabolism is controlled antagonistically by insulin and cortisol via amplification and desensitisation of the insulin signal from the insulin receptor. Normal aging of mammalian brains is associated with numerous inherent metabolic changes. The metabolic changes that are of pivotal importance include probable primary inherent variations in the neuronal insulin receptor, the desensitisation of the neuronal insulin receptor by circulating cortisol and receptor dysfunction subsequent to changes in membrane structure and function.
Elektronische Reproduktion der Druck-Ausgabe 27. Oktober 2012
Gesehen am 20.11.2025